Increasing Age Is a Risk Factor for Decreased Postpartum Pelvic Floor Strength. Issue 2 (March 2017) - Quiroz, Lieschen H.; Pickett, Stephanie D.; Peck, Jennifer D.; Rostaminia, Ghazaleh; Stone, Daniel E.; Shobeiri, S. Abbas
Abstract : Objectives: This study aimed to determine factors associated with decreased pelvic floor strength (PFS) after the first vaginal delivery (VD) in a cohort of low-risk women. Methods: This is a secondary analysis of a prospective study examining the risk of pelvic floor injury in a cohort of primiparous women. All recruited participants underwent an examination, three-dimensional ultrasound and measurement of PFS in the third trimester and repeated at 4 weeks to 6 months postpartum using a perineometer. Results: There were 84 women recruited for the study, and 70 completed the postpartum assessment. Average age was 28.4 years (standard deviation, 4.8). There were 46 (66%) subjects with a VD and 24 (34%) with a cesarean delivery who labored. Decreased PFS was observed more frequently in the VD group compared with the cesarean delivery group (68% vs 42%, P = 0.03). In modified Poisson regression models controlling for mode of delivery and time of postpartum assessment, women who were aged 25 to 29 years (risk ratio = 2.80, 95% confidence interval, 1.03–7.57) and 30 years and older (risk ratio = 2.53, 95% confidence interval, 0.93–6.86) were over 2.5 times more likely to have decreased postpartum PFS compared with women younger than 25 years. Conclusions: In this population, women aged 25 years and older were more than twice as likely to have a decrease in postpartum PFS.